ECENG GONDOK SEBAGAI MEDIA EDUKATIF DALAM PEMBELAJARAN MUATAN LOKAL DI SEKOLAH DASAR - Devi Ristyana Puji Lestari; Heru Subrata; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is the main foundation in shaping the character and abilities of the younger generation. In Indonesia, the education curriculum continues to be adapted to current developments and local needs, including the introduction and preservation of local culture and wisdom through local content in elementary schools. Water hyacinth (Eichornia crassipes), although often considered a weed, has great potential as an educational medium. This research uses a qualitative approach with descriptive methods to explore the use of water hyacinth as an educational medium in local content learning at Krian 2 State Elementary School. Through data collection techniques in the form of in-depth interviews, direct observation, and documentation, this research reveals that the use of water hyacinth as a material teaching successfully increases student engagement, environmental understanding, as well as practical skills and creativity. Students are involved in the process of collecting, processing and utilizing water hyacinth to make various craft products, which not only provides practical experience but also increases their environmental awareness. The results of the research show that the use of water hyacinth in local content learning has a positive impact on students' understanding of local wisdom and environmental conservation. Students learn the values ​​of hard work, perseverance, responsibility, and cooperation through water hyacinth-based activities. This implementation is also relevant to the local content curriculum and can support community economic empowerment through the introduction of the concept of entrepreneurship. The conclusion of this research shows that water hyacinth has great potential as an educational medium, providing broad educational benefits, as well as forming students' characters who care about the environment and have an entrepreneurial spirit. Recommendations for further development include training and support for teachers, collaboration with local communities, and ongoing evaluation to ensure the success and sustainability of using water hyacinth as an educational medium.